A Study on Adapting of Afghan Students in Universities of Turkey (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of the study is to propose a solution by examining the adaptation problems experienced by the Afghan students who are studying in different faculties and departments of various universities of Turkey. The survey based on the primary data collected by online sampling method and 60 different questions from Afghan students studying in Turkey by August 2017. In the analysis of the obtained data, SPSS version 21.0 program was used and parametric and nonparametric analysis techniques applied in the direction of research findings. The survey has been done in 49 various universities, 12 different faculties, and 161 students. Among the participants 39.1% had scholarships from the Turkish government (YTB), 26.7% were supported by the Afghanistan government, and 34.2% were studying by their own financial possibilities. All of the students came from Afghanistan for education purposes. Their parents’ economic and educational levels are good; nearly all of them are well-educated people. Most of the students are living in dormitories, and they are happy to study in Turkey. They don’t have any problems with interpersonal relationships and cultural adaptation with other students in dorms, as well as with people in Turkey.